'From information to interaction': website and social media usage and trends in top Indian higher education institutions. (2018) - Tripathi, Rakhi
The purpose of this study is to examine Web 2.0 usage in terms of website development and social media of top 300 higher education institutions (HEI) in India in terms of website and social media. Top 300+ institutions were selected from National Institutional Ranking Framework, India. Content analysis was used in terms of quantitative approach. All the selected institutions have website and one third of the institutions are on social media. One-fourth has unofficial accounts on social media. In totality no trend has been noticed in Web 2.0 usage of higher education institutions in India. This study is completely based on publicly available data regarding presence on website and social media. Outcomes suggest that HEI are using Web 2.0 applications but at a slow pace. This is the first research that draws an overall picture of the top institutions' Web 2.0 usage in India. The study provides academics with helpful information to better meet their user needs by effectively applying digital strategies.